An ultra-sensitive flexible piezoelectric nanogenerator based on P(VDF-TrFE) nanofibers - Haiyang Hu; Wei Li; Xingjia Li; Yu Xu; Xiaoming Zhao; Xiaoyue Huang; Shenglan Hao; Guangdi Feng; Qiuxiang Zhu; Xiuli Zhang; Chungang Duan; Junhao Chu; et al. (International Journal of Extreme Manufacturing, 2025)
Piezoelectric nanogenerators (PENGs) are evolving as next-generation energy harvesters due to their self-powered sensing, multi-stimuli-responsiveness, and wearable electronics. Here, we present a flexible PENG utilizing electrospun poly(vinylidene fluoride trifluoroethylene) (P(VDF-TrFE)) nanofibers. By optimizing the rotational speeds during the electrospinning process, we have achieved nanofibers with a highly aligned structure and uniform polar β-phase, an enhancement of piezoelectric response, particularly in terms of sensitivity and power generation. The longitudinal piezoelectric coefficient ( d _33 ) reaches −21.6 pC·N ^−1 . The transverse piezoelectric measurement yields an output of 26 V and 38.6 nA. The device exhibits an ultra-high sensitivity of 5.76 V·kPa ^−1 , surpassing previously reported values by orders of magnitude. The PENG is successfully employed for Braille recognition and the precise manipulation of a robotic hand, indicating its efficacy for tactile interaction systems. This study presents a novel approach to facilitating intelligent human-machine interaction by exploiting the unique properties of organic piezoelectric materials.